Sources and interpretation in ancient Judaism: studies for Tal Ilan at sixty - Pioṭrḳovsḳi, Meron M.; Herman, Geoffrey; Dönitz, Saskia; Ilan, Ṭal (Ancient Judaism and early Christianity, 2018)
Front Matter -- Copyright Page -- Preface and Acknowledgements -- Abbreviations -- Notes on Contributors -- Tabula Gratulatoria -- Introduction -- Second Temple Literature and History -- Chasing Away Lions and Weaving: The longue durée of Talmudic Gender Icons /Yosef Garfinkel -- Malthace, Archelaus, and Herod Antipas: Between Genealogy and Typology /Daniel R. Schwartz -- A New Perspective on Two Jewish Queens in the Second Temple Period: Alexandra of Judaea and Helene of Adiabene /Etka Liebowitz -- Was Hillel a Pharisee? /Cana Werman -- The Jews and the Papyri -- Ezechiel 33,21–39,29: Anmerkungen zum Profil der Sinneinheit in der nicht-masoretischen Textfassung (Papyrus 967) und zu Veränderungen durch proto-masoretische Redaktoren /Karin Finsterbusch -- The Third Century BCE: New Light on Egyptian Jewish History from the Papyri /Noah Hacham -- ‘Literary Jews:’ The Jewish Community of Oxyrhynchus in Light of Non-documentary Texts on Papyrus /Meron M. Piotrkowski -- Shabtai in Egypt: Cultural Interaction between Jews and Egyptians under the Ptolemies /Zsuzsanna Szántó -- Rabbinic Literature -- Babylonia of Pure Lineage: Notes on Babylonian Jewish Toponymy /Geoffrey Herman -- A Spindle for Caesar’s Daughter /Reuven Kiperwasser -- Rabbinic Forensics: Distinguishing Egg White from Semen in born Giṭṭin 57a /Judith R. Baskin -- Rabbinic Images of Second Temple Diasporas and Their Links with Judaea: History or Fantasy? /Isaiah Gafni -- Are Parables an Interpretation? /Ronit Nikolsky -- When a Man Sells His Daughter as an ‮אמה‬: The ‮אמה העבריה‬ as m. Qiddushin’s Role Model for Becoming a Wife /Judith von Bresinsky -- Classroom Encounters—An Appreciation /Christiane Hannah Tzuberi -- List of Publications of Prof. Tal Ilan.